Toward More Secure Software. - Denning, Dorothy E. (Communications of the ACM, 2015)
The article examines two proposals intended to reduce the number of software security flaws, the first of which calls for the U.S. government to corner the vulnerability market and the second which calls for holding companies liable for faulty software. Topics include software bug bounty programs run by large software companies that reward private individuals for uncovering security flaws; a discussion of the incentivization of both programs; and the way current licensing laws shield software companies from damages arising from faults in their products.